Українські прамовні діалектизми в індоєвропейській ретроспективі - Нечитайло, Ірина (Slavia Orientalis, 2025)
The article is devoted to a semantic evolution of the Proto-Slavic dialects of Ukrainian and their correlates in other Indo-European languages. The purpose of this article is to study their semantic transformations from Proto-Indo-European times to the present. The article identifies their Indo-European and Slavic preforms, corrects those of them presented in the etymological literature; examines the types of semantic transformations of Proto-Slavic dialects on the axis of Proto-Indo-European language – Proto-Slavic language – from which ancient and modern Slavic languages and dialects are established; outlined are the dialectal zones of concentration for these lingual reflexes.